FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI PADI SAWAH DI NAGARI BALAI PANJANG KECAMATAN LAREH SAGO HALABAN KABUPATEN LIMA PULUH KOTA, PROVINSI SUMATERA BARAT - Rahmad Karim; Ujang Paman (DINAMIKA PERTANIAN, 2023)
Rice is an important crop to provide staple food for majority of Indonesian. Therefore, rice must be produced continuously in sufficient amount to fulfil the need of population food every years. Paddy field is dominan and the number of production is affected by using producton factors (inputs). The purposes of this research are to examine the factors affecting rice production and to calculate cost, production, revenue, profit, and efficiency. The research used survey method and located in Lareh Sago Halaban District, Lima Puluh Kota Regency, Sumatera Barat Province. The research was conducted during 6 (six) months from January to June 2022. A total of 42 samples was selected randomly from 135 farmers’ group from 8 villages. Statistical and mthematics techniques were used to analyze data. Based on statistical analysis by using multiple-regression model of Cobb-dauglas function production, it was found that land area, seeds, labors, urea fertilizer, TSP fertilizer, KCl fertilizer, organic fertilizer, insecticide, herbicide, and fungicide significantly affected rice production. The production costs were an average of IDR 4,732,936.84/cultivated area/growing season with 2,304.29 kg/cultivated area/growing season on average and land area averaged 0.41 ha. The revenue was IDR 10,369,285.71/cuktivated area/growing season and profit was IDR 6,980,657.21/cultivated area/ growing season on average with efficiency value of 1.74.